Influence of the hypothalamic arcuate nucleus on intraocular pressure and the role of opioid peptides. - Ji Jin; Guo-xu Xu; Zhi-lan Yuan (PLoS ONE)
Background An opioid peptide neuron/humoral feedback regulation might be involved in changes of intraocular pressure (IOP). The aims of this study are to investigate the effects of arcuate nucleus (ARC) and opioid peptides on intraocular pressure (IOP). Methods Fifty-four healthy purebred New Zealand white rabbits (108 eyes) were randomly divided into 4 groups, including control group, electrical stimulation group, [D-Ala2, N-Me-Phe4, Gly5-ol]-enkephalin (DAMGO) group, and [D-Pen 2, D-Pen5]- enkephalin (DPDPE) group. Bilateral IOP was measured after unilateral electrical stimulation of the ARC or unilateral microinjection into the ARC of the selective μ-opioid receptor agonist DAMGO or the selective δ opioid receptor agonist DPDPE, both alone and after pre-administration of either the non-selective opioid receptor antagonist naloxone or saline. Results Both electrical stimulation in ARC and micro-injection either <mu> or <delta> opioid receptor agonists, DAMGO or DPDPE, respectively, caused a significant bilateral reduction in IOP (P<0.05) which was more pronounced in the ipsilateral than in the contralateral eye. Pretreatment with naloxone prevented some, but not all IOP reductions. Conclusion The ARC takes part in the negative regulation of IOP, an action that may involve opioid neurons.